The phantom Holocaust : Soviet cinema and Jewish catastrophe - Gershenson, Olga, 1969- (Jewish cultures of the world., 2013)
Focusing on work by both celebrated and unknown Soviet directors and screenwriters, this is a book about Soviet narrative films dealing with the Holocaust from 1938 to 1991. In addition to studying the completed films, it analyzes the projects that were banned at various stages of production. Archival research and in-depth interviews are used to tell the stories of filmmakers who found authentic ways to represent the Holocaust in the face of official silencing.